Structure, agency and community: Using online music gatherings to support social inclusion for people with disabilities in Australia during the COVID-19 pandemic. Issue 3 (27th May 2022) - McFerran, Katrina; Skinner, Anthea; Hall, Teresa; Thompson, Grace
ABSTRACT: Introduction: In the wake of COVID-19 restrictions and lockdowns in the southern states of Australia, many community music and music therapy projects shifted to an online format. This paper discusses the formation and creation of four online music groups aimed at people with disability, including two groups for children and two for adults. The aim of the study was to explore the use of online technologies to support social inclusion and wellbeing when participants were physically isolated. Method: This study positioned group participants as co-researchers to recognize the expertise many people with disability hold from being housebound or socially isolated. We adopted an action research framework in which participants provided ongoing reflections on the use of technology, access, musical foci and social interaction to iteratively develop the sessions through cycles of reflexive action. These data were triangulated with data collected through participant observation and individual interviews. Results: The structured format of the sessions created online spaces for people with different disability, age and gender identities to explore their creativity together. Far from limiting participants' autonomy and safety, the structured setting promoted their agency in decision-making and shaping the groups to meet their needs. Discussion: Many participants interacted with the group or adapted to the online experiences in ways which the authors had not anticipated. While we were expecting our cohort to have expertise with social isolation, we found that they also had high levels of expertise as passionate musicians, which they used to frame the activities of the online gatherings.